Slammeurs et public : une coparticipation performative (Altre Modernità, 2022)
Slam is a practice of writing and public speaking combining poetry and live performance. It was born in the United States at the end of the 1980s and arrived a decade later in France.In the last two decades, it has been one of the most emerging forms of oral literature, a neo-orature (Bobillot, Quand 114) presenting its aesthetic forms, rules, and a specific communication contract. After a brief historical review, our analysis proposes to explore its performative modalities, focusing on the dynamics of poetic co-creation that emerges from the influence between slammers and the public.
Keywords: Slam; poetry; performance; French literature; public; co-creation